Monetarism - Stein, Jerome L.; National Science Foundation (U.S.) (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier Pub. Co., 1976)
This book was a proceedings of a conference aimed at addressing the problems troubling the national economy US. It examines the views of monetarists groups and that of neo-Keynesians in providing solution to problems in the national economy.
Based on a conference sponsored by the National Science Foundation.
Includes bibliographies and index.
usc 28/08/2017
Loans
Keywords: Monetary policy; Fiscal policy; Chicago school of economics